Policy Formulations to Establish More Dry Port Infrastructures to Increase Seaport Efficiency, Productivity, and Competitiveness in Bangladesh - Razon Chandra Saha; Khairir Bin Khalil (Future Transportation)
Maritime trade in Bangladesh is growing significantly, as observed by UNCTAD, which reported 3.20 mTEUs throughput in 2022. Additionally, the principal seaport, Chattogram Port, reported a port throughput of 3.27 mTEUs in 2024, the historical record for any port in Bangladesh. More than 50% of imports and exports, including empty containers, were handled in 2024 through 19 nos close dry ports in Chattogram City by applying small-scale intermodal systems, where the performance of pure intermodal from/to mid-range dry ports (3 Nos) to Chattogram Port is 2.53%. By 2030, the government wants all import and export operations to be conducted through dry ports. Furthermore, the current volume of international goods freight cannot be handled by the dry ports that are currently in place. This research applied mixed methods to explore the opportunities to set more dry ports and the application of intermodal systems for increasing the seaport’s efficiency, productivity, and competitiveness. The Focus Group Discussion (FGD) method was used to know the dry port location, investment, and policy in creating the opportunity to set up more dry ports in Bangladesh. In the findings, 82.50% of participants agreed that existing facilities are not enough and need to establish more dry ports to handle current and future volumes of containers. Moreover, the responses reveal a division of opinion on establishing a dry port outside of Chattogram, with a notable inclination towards opposition. According to 62% of respondents, dry ports outside Chattogram are necessary. To enhance intermodal connectivity and facilitate easier cargo transfers between ports and hinterland regions, integrated infrastructure development would be in line with national economic objectives. The research aims to investigate the possibilities for establishing additional dry ports across the country to boost seaport productivity, efficiency, and competitiveness by utilizing intermodal freight transportation systems to cut costs and time while also considering environmental factors like CO2 emissions.